EPA and DHA inhibit LDL-induced upregulation of human adipose tissue NLRP3 inflammasome/IL-1β pathway and its association with diabetes risk factors - Valérie Lamantia; Simon Bissonnette; Myriam Beaudry; Yannick Cyr; Christine Des Rosiers; Alexis Baass; May Faraj (Scientific Reports)
Abstract Elevated numbers of atherogenic lipoproteins (apoB) predict the incidence of type 2 diabetes (T2D). We reported that this may be mediated via the activation of the NLRP3 inflammasome, as low-density lipoproteins (LDL) induce interleukin-1 beta (IL-1β) secretion from human white adipose tissue (WAT) and macrophages. However, mitigating nutritional approaches remained unknown. We tested whether omega-3 eicosapentaenoic and docosahexaenoic acids (EPA and DHA) treat LDL-induced upregulation of WAT IL-1β-secretion and its relation to T2D risk factors. Twelve-week intervention with EPA and DHA (2.7 g/day, Webber Naturals) abolished baseline group-differences in WAT IL-1β-secretion between subjects with high-apoB (N = 17) and low-apoB (N = 16) separated around median plasma apoB. Post-intervention LDL failed to trigger IL-1β-secretion and inhibited it in lipopolysaccharide-stimulated WAT. Omega-3 supplementation also improved β-cell function and postprandial fat metabolism in association with higher blood EPA and mostly DHA. It also blunted the association of WAT NLRP3 and IL1B expression and IL-1β-secretion with multiple cardiometabolic risk factors including adiposity. Ex vivo, EPA and DHA inhibited WAT IL-1β-secretion in a dose-dependent manner. In conclusion, EPA and DHA treat LDL-induced upregulation of WAT NLRP3 inflammasome/IL-1β pathway and related T2D risk factors. This may aid in the prevention of T2D and related morbidities in subjects with high-apoB. Clinical Trail Registration ClinicalTrials.gov (NCT04496154): Omega-3 to Reduce Diabetes Risk in Subjects with High Number of Particles That Carry “Bad Cholesterol” in the Blood – Full Text View - ClinicalTrials.gov.